Studies on Antioxidant and Antineoplastic Potentials of Oldenlandia corymbosa Linn. Leaves - Md. Abdul Aziz; Md. Julkar Nime; Md. Habibur Rahman; Ziasmin Khatun; Md. Rowshanul Habib; Ayesha Siddika; Marina Khatun; Md. Rezaul Karim (Journal of Fundamental and Applied Pharmaceutical Science, 2023)
Various bioactive properties, including antioxidant and antineoplastic properties, are extracted from plant species. Oldenlandia corymbosa Linn. is an important medicinal plant that grows as a weedy annual herb throughout Bangladesh. However, no previous studies have reported the antineoplastic and antioxidant potentials of Oldenlandia corymbosa leaves. Based on this fact, this investigation evaluated the methanol extract of Oldenlandia corymbosa Linn. leaves (MELO) for its antioxidant and antineoplastic properties. Different in vitro experiments were applied here to measure the phytochemical content and antioxidant activity of MELO. Functional assays were utilized to measure the antineoplastic activity of MELO against Ehrlich Ascites Carcinoma (EAC) in mice. MELO contains rich phenolic compounds, flavonoids, flavonol, and proanthocyanidin. In vitro antioxidant assay, MELO exhibited significant ABTS▪ (IC50: 98.07 μg/mL) and DPPH (IC50: 151.21μg/mL) radicals scavenging activity when compared with the positive control (Ascorbic acid). MELO also showed total antioxidant and ferrous-reducing properties. In the antineoplastic study, dose-dependent reduction in viable EAC cell count was observed in MELO-treated groups. In contrast, treatment with MELO significantly (P0.05) increased the mean survival time and life span (65.21%) of EAC-bearing mice. The altered hematological parameters of mice of the EAC control group were restored to the normal level by treating MELO. MELO also induced the apoptotic features observed in the morphology of DAPI-stained EAC cells. As identified by GC/MS analysis, the Phytochemical profiles of MELO are also consistent with their antioxidant, antineoplastic and apoptotic properties. Thus, the methanol extract of Oldenlandia corymbosa leaves (MELO) has the potential to consider a good source of antioxidants and antineoplastic agents.